Pengaruh Inflasi dan Tingkat Pengangguran Terhadap Pertumbuhan Ekonomi Makro di Indonesia - Hazlin, Nur Azra Amanda; Al-Musli, Siti Aisyah Zaskia; Khalid, Muhammad; Gunawan, Agung (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the factors influencing economic growth in Indonesia, focusing on inflation and the unemployment rate as the main variables. The data used in this study are sourced from official publications of the Central Statistics Agency (BPS) and Bank Indonesia for a specific period. The analysis was was conducted using Ordinary Least Squares (OLS) which used the data from 2011-2015 per semester. The results show that inflation has a negative and significant effect on economic growth, where rising inflation tends to reduce people's purchasing power and lower investment levels. Furthermore, the unemployment rate also has a negative effect on economic growth, reflecting that high unemployment can hamper productivity and domestic consumption. These findings emphasize the importance of maintaining price stability and creating productive jobs as key factors in supporting sustainable macroeconomic growth in Indonesia. Based on these results, this study recommends that the government continue to control the inflation rate through effective monetary policy and enhance human resource development programs and the creation of quality jobs to support inclusive and sustainable economic growth.